2020
DOI: 10.1007/s13300-020-00843-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reasons for Treatment Discontinuation, Attitudes and Education Needs Among People Who Discontinue Type 2 Diabetes Treatment: Results from an Online Patient Survey in the USA and UK

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) requires long-term treatment to achieve and maintain glycaemic control; however, up to 50% of people with T2DM discontinue treatment by 1 year. It is therefore important to understand the patient perspective of therapeutic adherence and persistence. Methods: An online questionnaire was presented to people with T2DM in the USA and UK on PatientLive Ò , a platform of Carenity, an online patient community. Those who discontinued at least one T2DM treatment within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
(38 reference statements)
1
29
0
Order By: Relevance
“… 48 The quantitative findings from the discontinuation studies reported herein are also consistent with the qualitative evidence from various surveys where weight gain was reported to be a common reason for treatment discontinuation among people with T2D. 49–51 For example, in a multinational online survey evaluating persistence with basal insulin, it was reported that weight gain was one of the most common reasons for interruption or discontinuation of therapy in 44.2% and 37.6% of survey respondents, respectively. 50 Another survey in an online patient community found that 18% of respondents in the USA and UK who had discontinued at least one medication in the previous 6 months (including OADs, insulin, and GLP-1 RAs) did so because of weight gain.…”
Section: Discussionsupporting
confidence: 84%
“… 48 The quantitative findings from the discontinuation studies reported herein are also consistent with the qualitative evidence from various surveys where weight gain was reported to be a common reason for treatment discontinuation among people with T2D. 49–51 For example, in a multinational online survey evaluating persistence with basal insulin, it was reported that weight gain was one of the most common reasons for interruption or discontinuation of therapy in 44.2% and 37.6% of survey respondents, respectively. 50 Another survey in an online patient community found that 18% of respondents in the USA and UK who had discontinued at least one medication in the previous 6 months (including OADs, insulin, and GLP-1 RAs) did so because of weight gain.…”
Section: Discussionsupporting
confidence: 84%
“…GI-related TEAEs are among the most frequent reasons provided for treatment discontinuation of GLP-1 RAs [23], and are an important determinant of tolerability. The time courses of GIrelated TEAEs and other tolerability indicators for dulaglutide 1.5, 3.0, and 4.5 mg are important factors for patients and health-care providers to consider when initiating or escalating dulaglutide doses.…”
Section: Discussionmentioning
confidence: 99%
“…Few patients who escalated from 1.5 to 3.0 mg and subsequently to 4.5 mg in 4-week increments experienced new or additional GI TEAEs, and for those patients who did, most were mild in severity. Patients' reports of tolerability concerns contribute to poor treatment adherence [23,31]. Providing tolerability information associated with dulaglutide 3.0 mg and 4.5 mg to patients during consultation for dose escalation may improve adherence to a medication regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment complexity and convenience have been widely recognized to affect adherence to medications. [37][38][39] It has been suggested that decreasing the frequency of daily doses and using insulin pens instead of insulin vial may improve adherence. 37,39 However, in the context of Indonesia, the use of insulin pens may provide further burden related to accessibility and cost.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has shown that experiences of adverse effects have led to discontinuing the medications. [37][38][39]51 Social activities may also affect people's behavior in taking medications. Many participants in this study mentioned that they often skipped taking medications when they were busy with social activities, such as family gathering or other social activities.…”
mentioning
confidence: 99%